Differential cytokine contributions of perivascular haematopoietic stem cell niches - Asada, Noboru (Nat Cell Biol, 2017)
Arterioles and sinusoids of the bone marrow (BM) are accompanied by stromal cells that express nerve/glial antigen 2 (NG2) and leptin receptor (LepR), and constitute specialised niches that regulate quiescence and proliferation of haematopoietic stem cells (HSCs). However, how niche cells differentially regulate HSC functions remains unknown. Here, we show that the effects of cytokines regulating HSC functions are dependent on the producing cell sources. Deletion of chemokine C-X-C motif ligand 12 (Cxcl12) or stem cell factor (Scf) from all perivascular cells marked by Nestin-GFP dramatically depleted BM HSCs. Selective Cxcl12 deletion from arteriolar NG2(+) cells, but not from sinusoidal LepR(+) cells, caused HSC reductions and altered HSC localisation in BM. By contrast, deletion of Scf in LepR(+) cells, but not NG2(+) cells, led to reductions in BM HSC numbers. These results uncover distinct contributions of cytokines derived from perivascular cells in separate vascular niches to HSC maintenance.